1995
DOI: 10.1089/dna.1995.14.961
|View full text |Cite
|
Sign up to set email alerts
|

Binding of a CTF/NF1-Like Protein to the Mouse Colony-Stimulating Factor-1 Gene Promoter

Abstract: Circulating and tissue-specific monocytes/macrophages, through production of hydrolytic enzymes and growth factors, can dramatically affect the local tissue environment. Colony-stimulating factor-1 (CSF-1) is a key regulator of monocyte/macrophage cell activity. CSF-1 is produced by stromal elements, including fibroblasts, which are found in all tissues. To understand at the molecular level how changes in CSF-1 gene transcription are initiated in fibroblasts, we set out to identify the cis-acting elements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…7). Mutations in CTF/NF1 binding sites have been shown to decrease transcriptional activity in other promoters (39,40). Most notably, we found an A>G mutation at the transcription initiation site in conserved element I, only present in the X M Xist allele (Fig.…”
Section: Somatic Inactivation Of the X P Chromosomementioning
confidence: 57%
“…7). Mutations in CTF/NF1 binding sites have been shown to decrease transcriptional activity in other promoters (39,40). Most notably, we found an A>G mutation at the transcription initiation site in conserved element I, only present in the X M Xist allele (Fig.…”
Section: Somatic Inactivation Of the X P Chromosomementioning
confidence: 57%
“…Genes implicated in fibrosis and ECM remodeling were also included, such as Wisp2, a member of the WNT/␤-catenin pathway, Pdgfr␣, one of the PDGF receptors, and Ahr, a ligand-activated transcriptional factor (6,7,9). Finally, Csf1 was also included, due to the identification of an NFI-C binding site in its promoter (27). Transcripts were extracted from four matched pairs of embryonic fibroblasts obtained from NFI-C knockout mice and their respective wild-type littermate controls.…”
Section: Resultsmentioning
confidence: 99%
“…When the mutated CTF/NF1 site was introduced into a truncated CSF-1 reporter constructs (nts 2100 to 1183), there was still no effect on CSF-1 reporter construct activity. At this point, we concluded that the activity of CSF-1 reporter constructs spanning nts 288 to 1183 is the result of proteins binding to the serum-induced element located in the region between nts 262 and 254 and/or to the 2 GC boxes located in the region between nts 243 and 228 (Konicek et al, 1995). Studies to confirm this are ongoing in our lab.…”
Section: Protein Binding To the Regionmentioning
confidence: 77%
“…Data are presented as the average positive standard deviation of duplicated samples from 3 separate transfections. (Reproduced, with permission, fromKonicek et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation